Factors Affecting the Work Engagement of Healthcare Workers during the COVID-19 Pandemic - Erlian Indah Mustikawati; Ernawaty Ernawaty (Unnes Journal of Public Health, 2023)
The COVID-19 Pandemic is a challenge for the world and, foremost, the healthcare system. The high intensity of work, the high risk of exposure, and the mental burden due to COVID-19 can affect the work engagement of healthcare workers. Healthcare worker engagement tends to be low. This research aimed to identify the factors that affect the work engagement of healthcare workers during the COVID-19 Pandemic. This research was a scoping review study conducted in December 2022. The keywords used were "work engagement," "healthcare worker," "healthcare," and "COVID-19" in the PubMed, Science Direct, and ProQuest databases. The criteria used were original articles written in English and published during 2020-2022. Outcome mapping based on PRISMA-ScR. A number of 19 articles were classified into job resources, personal resources, job demands, and demographic factors. Most of the articles were published in 2022 (52%), conducted in China (32%), had a cross-sectional research design (79%), and stated that healthcare workers are tied to work during the COVID-19 Pandemic (37%). The most common factors affecting workforce engagement found in the selected articles were job resources and job demands (47%). Healthcare workers' engagement level during the COVID-19 Pandemic was classified as moderate and high. The research found four factors affecting healthcare workers' work engagement during the COVID-19 Pandemic: job resources, personal resources, job demands, and demographic factors. Future research is expected to examine how to keep healthcare workers engaged in extreme situations such as the COVID-19 Pandemic.